Effect of post-curing regime on density, compressive strength and crosslinking of polymer concrete - Nur, N.; Hussin, M.; Ismail, Mohamed; Ismail, M.A.; Mohamed, A.; Ariffin, N.; Abdul Shukor Lim, N.; Samadi, M. (Penerbit Universiti Teknologi Malaysia, 2015)
© 2015 Penerbit UTM Press. All rights reserved. Polymer concrete is produced from polymer binder, aggregates, and filler. Its curing follows the polymerization process once polymer additive is added, and can be accelerated through post-curing. In this study, the Orthophthalic- and Isophthalic-based polymer concrete (Ortho-PC and Iso-PC) were cured and investigated at different curing temperature (30°C, 50°C and 70°C) and period (1, 3, 6, 16, 24 hours) to complete the compressive strength development. Effect of curing temperature and period on apparent density, compressive strength, and morphology properties were investigated. The outcomes exhibited that all specimens had achieved full compressive strength within 6 hours of curing time at both 50°C and 70°C. When cured at 30°C, this went up to more than 16 hours of curing period to achieve the same compressive strength. The form of crosslinking at different curing conditions was captured in Scanning Electron Microscope, SEM images. Results also showed that curing temperature and period insignificant affected the apparent density. This study can be used as references to manufacturer, fabricator, and engineers when dealing with polymer concrete which goes for post-curing method as curing process.